Essence of the Information Product and its Defects - Mohamed Hassan Abdullah, (International Journal of Law Research and Studies, 2025)
The research deals with the concept of "information product", especially computer software and artificial intelligence systems, and analyses its technical and legal nature and the producer's responsibility for its defects. It explains that the debate over the classification of software began in the eighties, as legislation and the judiciary differed between considering it as mere software instructions, a stand-alone product, or part of computer hardware. With the development of technology, the need for a more accurate classification of this software increased, especially with the emergence of artificial intelligence systems. The research highlights the challenges of legal adaptation of software in different legislations, as its legal protection varies between intellectual property laws, criminal laws, and judicial rulings. It also discusses the new European directive on liability for defective products, which recognizes software as an independent product, and determines the producer's responsibility for its defects. The research also deals with the concept of information defect compared to traditional defects in physical products, explaining that software may be subject to defects in design, manufacturing (setup), or lack or deficiency in warnings. The research raises fundamental questions about the possibility of applying traditional product liability standards to information products, especially with regard to assigning responsibility when damage occurs due to a fault or defect in the software or artificial intelligence system. In conclusion, the research proposes adopting the concept of "information product", with the development of legal frameworks that accommodate its hybrid nature, and determine the responsibilities of producers and users according to the levels of risk control. It also emphasizes the need to update legislation to keep pace with rapid developments in artificial intelligence, - especially - with regard to liability for unexpected errors and independent decisions of these systems.
Keywords: Information Product; Computer Program; Artificial Intelligence System; Information Defect; Information Defect Proof